UPDATE TO THE LEGEND OF THE RECONNAISSANCE SOIL MAP OF ESPÍRITO SANTO STATE AND THE IM - PLEMENTATION OF GEOBASES INTERFACE FOR DATA USAGE IN GIS - Alexson de Mello Cunha,; Hideko Nagatani Feitoza,; Leandro Roberto Feitoza,; Fernando Soares de Oliveira,; João Luiz Lani,; John Kennedy Ferreira Cardoso,; Filipe Silveira Trindade, (Geografares, 2016)
The objective of this study was the upgrade of soil mapping units defined in surveys published by the Radambrasil/ IBGE in 1983 and 1987, with the main focus on the classes ofsoils. To accomplish this, data from representative soil profiles of those surveys were used to classify them in the current Brazilian Classification System. The mapping units which do not have representative profiles wereupdated based solely on the direct correlation between the denomination used in the old and current classification. Thiswork has also updated the legend of the reconnaissance soil map. The layer of information related to soil, in shape format, containing an attribute table with data regarding mapping units and the respective updated legends (taxonomy, symbols and colors) is currently available and can be downloaded by the general public using the Geobases browser. A specific geographic interface for the partners of Geobases dedicated to soil studies has also been created. This interface allows the analysis, acquisition and input of new data, which contributes to the non-duplication of efforts and financialresources on activities of surveying, registering and maintenanceof geospatial database related to soils in the State.
Keywords: spatial data, geospatial data base, geographic information system